Simple Automatic Transfer Switch System Using Timer Delay Relay - Asni Tafrikhatin; Jati Sumarah; Ajeng Tiara Wulandari; Unggul Pambudi; Iftah Ghozy Allam (Politeknik Piksi Ganesha Indonesia, 2022)
A control system in the form of an Automatic Transfer Switch (ATS) is needed when a blackout occurs from the PLN that will be transferred to the generator. The research problem was how to save costs for making ATS that can run efficiently. The purpose of this study was to find out how to save costs for making ATS that can run well and efficient. The method used was Research and Development. The Research and Development stages included: collecting data, designing, and testing. To save costs for making ATS, the researchers used the Timer Delay Relay (TDR), as using TDR reduces the cost of making tools because the component prices are relatively affordable. The way the ATS system works is when the PLN electricity is on, the battery will be charged by the battery charger, and when the PLN electricity goes out, the inverter will get a voltage supply from the battery, that was originally 12V will be changed to 220V. The TDR makes it easier to determine the appropriate time when the voltage is stable. Based on the experiment, the time when the voltage is stable is 6 seconds.